Anal canal and rectal condylomatosis: exhaustive proctological examination and STD patients - Delbello, Alessandro (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2010)
Infection of the anorectal area with some subtypes of HPV virus results in local involvement that appears as warty, papillary, condylomatous lesions. Patients exposed to high-risk HPV types, such as HPV-16, -18, and -31, are at risk for developing high-grade dysplasias or carcinomas. We reviewed 15 years (1991 - 2006) of patient records from our proctological unit and STD center and found 1,122 patients affected by anorectal condylomatosis. This study supports the importance of an exhaustive proctological examination in patientssuffering from condylomatosis of the genital area, especially of the perianal zone, and in patients examined in the STD clinic, even for other reasons. An unknown anorectal condylomatosis is a frequent cause of relapse ofanogenital warts. Anal warts should be examined by proctoscopy to assess thefull extent of the lesions and prevent possible complications.
Keywords: anus; Anus Diseases; Anus, bolezni; Condylomata Acuminata; infekcije; Kondilomata akuminata; Papillomavirus, Human; papiloma virusi; Papilomavirus človeški; Proctoscopy; Proktoskopija; Rectal Diseases; Rektalne bolezni; virusne infekcije